PHYSICIAN BURNOUT LEVELS AND ASSOCIATED FACTORS IN THE COVID-19 PANDEMIC - Yilmaz, Sinan; Koşan, Zahide; Bilge Yerli, Ezel; Çınar Tanriverdi , Esra; İba Yılmaz , Sibel (Sanamed, 2023)
Introduction: Burnout, characterized by emotional exhaustion, depersonalization, and low personal accomplishment, is frequently observed in physicians. Aim: The purpose of this study was to determine burnout levels and associated factors in physicians during the pandemic.Material and Method: This cross-sectional study was performed online with 288 physicians from various fields in Erzurum. Sociodemographic questions and the Maslach Burnout Inventory represented the data collection tools. The data were collected online in May and June 2021. Statistical analysis: Descriptive statistics, Student's t and ANOVA tests And Multiple ordinal logistic regression analysis were used. p values
Keywords: Burnout; Physicians; COVID-19; Pandemic; Maslach Burnout Inventory